Pengaruh Tingkat Pendidikan Terhadap Kemampuan Aparatur Pemerintahan Nagari dalam Pengelolaan Keuangan Nagari - Khairani Khairani (Journal of Education on Social Science (JESS), 2019)
The purpose of this study was to determine the effect of level education on the performance of nagari apparatus in nagari financial management in Tanah Datar Regency. Background of this study was that there were indications that the financial management of nagari was still not good in Tanah Datar Regency. This research used quantitative research method. The population of this research was all of the nagari apparatus in Tanah Datar regency numbered 600 people consisting of walinagari, nagari secretaries, nagari treasurer and five head of nagari affairs. The sample in this research consisted of 245 respondents who were determined using the Slovin formula and through the Multi Stage Random Sampling technique. The data were collected through questionnaires. Data of this research were analyzed with Anova Test. The results in this research indicated no that there was significant difference in the performance of nagari financial management based on education level in Tanah Datar Regency.